THE EFFECT OF USING AN EDUCATIONAL PACKAGE ON SOME MOTOR ABILITIES AND THE ACCURACY OF PERFORMING CERTAIN HANDBALL SKILLS FOR FEMALE STUDENTS - Hassan Naji, Nisreen; Ahmed Kamel, Naseer (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
This study aims to examine the impact of an educational package on developing the motor abilities and handball skills of female students at the College of Education for Women. The study adopted an experimental method by dividing the sample into two groups: an experimental group that used the educational package and a control group that followed traditional methods. The educational package included multiple resources, such as sequential images, video discs, and booklets, to provide instant feedback and support self-learning. The results indicated a significant improvement in motor abilities like maximum speed, explosive power, and core strength, as well as handball skills, including passing, receiving, and shooting accuracy, confirming the effectiveness of the educational package in achieving learning objectives and skill development.